PELAKSANAAN PENGANGKATAN ANAK YANG MENYEBABKAN PEMUTUSAN HUBUNGAN NASAB DENGAN ORANG TUA KANDUNG DITINJAU DARI PERATURAN PEMERINTAH NOMOR 54 TAHUN 2007 TENTANG PELAKSANAAN PENGANGKATAN ANAK (STUDI DI DESA TANJUNG MEDAN, KABUPATEN LABUHAN BATU SELATAN) - Darnedy Kurnia Santi; T.Keizerina Devi A; Idha Aprilyana Sembiring; Yefrizawati - (jurnal.unprimdn.ac.id, 2022)
Adoption of a child is the transfer of a child from biological parents to adoptive parents, where the responsibility of the biological parents also shifts to the person who adopted him. However, there are discrepancies in the adoption process as happened in the Tanjung Medan Village area, South Labuhanbatu Regency, in this case there are people who adopt as many as 14 families, there are 5 families who take action to terminate the kinship relationship between the child's biological parents. with his son. This is of course not in accordance with Government Regulation Number 54 of 2007 concerning the Implementation of Child Adoption. The purpose of this study was to determine whether the process of implementing child adoption in Tanjung Medan Village, South Labuhanbatu Regency was in accordance with PP Number 54 of 2007, to determine the cause of the termination of kinship relations with biological parents during the adoption process that occurred in Tanjung Medan Village, Kabupaten Tanjung Medan. Labuhanbatu Selatan, and to find out that the legal protection for adopted children is not in accordance with the adoption process as regulated in PP number 54 of 2007. This research method uses a normative juridical approach and an empirical juridical approach. The data used are primary data and secondary data. All data were analyzed by qualitative data analysis method. Based on research, the implementation of child adoption in Tanjung Medan Village is currently not in accordance with Government Regulation Number 54 of 2007 concerning the Implementation of Child Adoption, therefore there is a need for cooperation between the village head and parents who want to adopt children to be given counseling about the implementation adoption of children in accordance with statutory regulations.